Higher glass transition temperatures reduce thermal stress cracking in aqueous solutions relevant to cryopreservation - Soheil Kavian; Ronald Sellers; Gabriel Arismendi Sanchez; Crysthal Alvarez; Guillermo Aguilar; Matthew J. Powell-Palm (Scientific Reports)
Abstract Cryopreservation by vitrification could transform fields ranging from organ transplantation to wildlife conservation, but critical physical challenges remain in scaling this approach from microscopic to macroscopic systems, including the threat of fracture due to accumulated thermal stresses. Here, we provide experimental and computational evidence that these stresses are strongly dependent on the glass transition temperature $$\:T_{g}$$ of the vitrification solution, a property which, given the narrow band of chemistries represented within common vitrification solutions, is seldom investigated in thermomechanical analyses. We develop a custom cryomacroscope platform to image glass cracking in four aqueous solution chemistries spanning > 50 °C in $$\:T_{g}$$ ; we process these images using semantic segmentation deep learning algorithms to analyze the extent of cracking in each; and we perform thermomechanical finite element simulations to disentangle the multiphysics effects driving the observed dependency, providing new insights to inform design of next-generation vitrification solutions that minimize thermal cracking risks.